AI-Enhanced Professional Development: Effects on Secondary EFL Teachers’ Digital Competencies and Affective Dimensions in Turkey - TÜTÜNİŞ, Birsen and ÜNAL, Kerim and KÖKSAL, Özge (Journal of Posthumanism, 2025)
This mixed-methods investigation examines the efficacy of structured artificial intelligence (AI) training on secondary-level English as a Foreign Language (EFL) teachers’ technological competencies and psychological dispositions within the Turkish educational context. AI technologies have a transformative potential for language acquisition processes, yet studies underlines that secondary EFL teachers frequently demonstrate insufficient proficiency in the selection and pedagogical implementation of appropriate AI applications. The integration of AI-based tools into language instruction presents significant opportunities for improving learner engagement and linguistic development. However, the actualization of these benefits remains contingent on teachers’ technological literacy and affective orientations. The present study employed a convergent parallel design to assess the impact of a comprehensive AI professional development program on 40 secondary EFL teachers across four dimensions: anxiety toward AI implementation, attitudinal orientations, perceptions of educational utility, and digital materials development competencies. Quantitative analyses revealed statistically significant improvements across all measured constructs: diminished anxiety levels (-14.1%), enhanced positive attitudes (+7.5%), more favorable perceptions of AI’s instructional value (+6.4%), and substantially improved digital materials creation skills (+18.5%). Furthermore, demographic variables functioned as significant moderators of intervention efficacy, with analyses indicating that younger female practitioners with prior technological experience demonstrated markedly greater improvements. A robust negative correlation (r = -0.634) between anxiety reduction and competency enhancement suggests that addressing affective barriers constitutes a critical prerequisite for developing teachers’ technological capabilities.These findings underscore the necessity for differentiated professional development frameworks that account for practitioners’ demographic characteristics and technological histories. By simultaneously addressing both technical competencies and psychological barriers to AI adoption, educational institutions can better prepare EFL teachers to support language acquisition in increasingly technology-mediated educational environments aligned with Common European Framework of References for Languages (CEFR) standards.